PENERAPAN METODE PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR SENI BUDAYA PADA SISWA KELAS VII-3 SMP NEGERI 14 BANDAR LAMPUNG SEMESTER GANJIL TAHUN PELAJARAN 2014/2015 - Efniati, Efniati (LPPM STKIP PGRI Bandar Lampung, 2015)
Difficulties in the learning process of students' art is not like the art lessons and teachers have not been able to raise student motivation, especially in the choice of teaching methods. To that end, the authors conducted a classroom action research in SMPN 14 Bandar Lampung in September-November 2014 through contextual learning model. The object of this study were students of class VII-3 amounted to 37 people. PTK includes: (1) planning, (2) implementation, (3) observation, and (4) reflection. Quantitative data collection is done through student worksheets and post test. Qualitative data collection activities conducted by observation, interviews, and student attitude scale. Results of the analysis of the data shows contextual learning model can improve student learning outcomes, namely in the first cycle of student learning outcomes completion percentage of 52.7%, the second cycle is 70.3%, and the third cycle is 82.4%. Learning activities of students in the first cycle was 52.7%, in the second cycle to 73% and the third cycle becomes 83.8%.